Metamorphosis of Heterostructured Surface‐Mounted Metal–Organic Frameworks Yielding Record Oxygen Evolution Mass Activities. Issue 38 (1st August 2021) - Hou, Shujin; Li, Weijin; Watzele, Sebastian; Kluge, Regina M.; Xue, Song; Yin, Shanshan; Jiang, Xinyu; Döblinger, Markus; Welle, Alexander; Garlyyev, Batyr; Koch, Max; Müller‐Buschbaum, Peter; et al.
Abstract: Materials derived from surface‐mounted metal–organic frameworks (SURMOFs) are promising electrocatalysts for the oxygen evolution reaction (OER). A series of mixed‐metal, heterostructured SURMOFs is fabricated by the facile layer‐by‐layer deposition method. The obtained materials reveal record‐high electrocatalyst mass activities of ≈2.90 kA g −1 at an overpotential of 300 mV in 0.1 m KOH, superior to the benchmarking precious and nonprecious metal electrocatalysts. This property is assigned to the particular in situ self‐reconstruction and self‐activation of the SURMOFs during the immersion and the electrochemical treatment in alkaline aqueous electrolytes, which allows for the generation of NiFe (oxy)hydroxide electrocatalyst materials of specific morphology and microstructure. Abstract : A facile strategy is developed to prepare highly active oxygen evolution reaction (OER) electrocatalysts by the in situ structural transformation and self‐activation of heterostructured surface‐mounted metal–organic frameworks (SURMOFs). This work enables access to a parameter space of metal‐oxyhydroxide‐type catalyst fabrication through the structural metamorphosis of SURMOFs.